Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.4028/p-1eiar8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Waste Glass Powder on Properties of Self-Compacting Repair Mortars

Abstract: This paper studies the effects of fine waste glass powder content (WGP) on fresh and hardened properties of self-compacting repair mortar mixes (SCRMs). For this purpose, mortar mixes were prepared to replace cement with waste glass powder ranging from 0 to 30% at 10% interval and tested. Fresh properties were assessed using mini-slump flow and mini V-funnel. Hardened properties assessed for all mixes were water absorption (at 28-days of age), compressive and flexural strengths (at 7, 28 and 56-days of age). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Amar et al 23 conducted a study to investigate the impact of waste glass powder dosage on the fresh and hardened properties of self-compacting repair mortar mixes. The findings revealed that the addition of glass powder had an adverse effect on the workability of the mortar.…”
Section: Introductionmentioning
confidence: 99%
“…Amar et al 23 conducted a study to investigate the impact of waste glass powder dosage on the fresh and hardened properties of self-compacting repair mortar mixes. The findings revealed that the addition of glass powder had an adverse effect on the workability of the mortar.…”
Section: Introductionmentioning
confidence: 99%